2016
DOI: 10.1111/bcp.12926
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of prophylactic levetiracetam in supratentorial brain tumour surgery: a systematic review and meta‐analysis

Abstract: AIMSThe aim of this study was to perform an up-to-date systematic review and meta-analysis on the efficacy and safety of prophylactic administration of levetiracetam in brain tumour patients. METHODA systematic review of studies published until April 2015 was conducted using Scopus/Elsevier, EMBASE and MEDLINE. The search was limited to articles reporting results from adult patients, suffering from brain tumour, undergoing supratentorial craniotomy for tumour resection or biopsy and administered levetiracetam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 62 publications
1
23
1
Order By: Relevance
“…Side effects of levetiracetam, which is the current drug of choice for most neuro-oncological patients requiring anticonvulsive treatment, include e.g. fatigue, insomnia, mood and behaviour changes, headaches and decreased white blood counts 21 , 22 . These effects of have to be weighed against the risk of recurrent seizures with its attendant socioeconomic sequelae (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects of levetiracetam, which is the current drug of choice for most neuro-oncological patients requiring anticonvulsive treatment, include e.g. fatigue, insomnia, mood and behaviour changes, headaches and decreased white blood counts 21 , 22 . These effects of have to be weighed against the risk of recurrent seizures with its attendant socioeconomic sequelae (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Newer generations of AEDs, e.g. Levetiracetam, have less adverse effects, have a potentially synergistic effect on oncologic treatment, as well as an antiemetic and neuro-protective effect compared to the older AEDs [3,4,14].…”
Section: Introductionmentioning
confidence: 99%
“…1 Furthermore, neither the tumor type nor the type of surgery influenced seizure activity. 30 Pourzitaki et al reported a meta-analysis of prophylactic levetiracetam usage in patients with brain tumors; 23 two of four studies included in the analysis investigated epilepsy patients with a his- tory of seizure disorders. Another meta-analysis by Yuan et al also included studies and patients with and without seizure history.…”
Section: Discussionmentioning
confidence: 99%